Experimental characterization of a bi-dimensional array of negative capacitance piezo-patches for vibroacoustic control. (May 2015) - Tateo, F; Collet, M; Ouisse, M; Ichchou, MN; Cunefare, KA; Abbe, P
This study presents an experimental investigation of the application of a periodic array of shunted piezoelectric patches with negative capacitance for the broadband control of waves propagating on a flexible plate. A 15 × 5 array of piezoelectric patches is bonded onto the top surface of a freely supported rectangular plate. The patch array is intended to serve as an active interface between two regions of the plate, where one region has an input disturbance force and the other does not. Each patch is shunted through a single circuit, reproducing a resistance in series with a negative capacitance. The magnitude of the reactive part of the negative shunting impedance is tuned close to the intrinsic capacitance of the piezoelectric patch. The real part is adjusted for either light damping so as to induce a reactive (reflective) response, or with heavy damping to induce greater absorption. The experimental responses of the system equipped with this active interface display a strong attenuation or reflection of vibrations, depending on the shunt resistance, over a large frequency range, including the mid-frequency regime. In an effort to control vibroacoustic phenomena, this study represents the first attempt to implement an integrated smart metacomposite active interface on a plate structure.